Resolving Grievances for Mutual Beneficence: Kang Jeungsan's Religious Framework for Social Justice in Early Modern Korea - Kim, Taesoo (Millah: Journal of Religious Studies, 2025)
This article examines the principle of 'resolving grievances for mutual beneficence' (Haewon-sangsaeng) in Kang Jeungsan's (1871-1909) Reordering Works, a series of religious rituals performed in early 20th-century Korea. These rituals addressed systemic inequities affecting various marginalized groups, including revolutionaries, economically disadvantaged people, lower classes, and women. While conventional approaches to social harmony typically emphasize political, institutional, or economic measures, Kang's framework distinctively integrates the resolution of grievances at both individual and collective levels. This approach emerges from an anthropocentric worldview that elevates human dignity while acknowledging the interconnection between the divine and human realms. Through an analysis of primary texts and comparative religious perspectives, this study demonstrates how Kang's principle of resolving grievances for mutual beneficence offers a comprehensive religious framework for achieving justice and peace by synthesizing personal transformation with broader social change.